Interplay between human papilloma virus infection and p53 gene alterations in head and neck squamous cell carcinoma of an Indian patient population. Issue 9 (1st November 2006) - Mitra, S; Banerjee, S; Misra, C; Singh, R K; Roy, A; Sengupta, A; Panda, C K; Roychoudhury, S
Abstract : Aim: To investigate the complex interplay between human papilloma virus (HPV) infection and p53 gene alteration in 92 head and neck squamous cell carcinoma (HNSCC) and 28 leukoplakia samples from eastern India. Methods: DNA isolated from the patient samples was subjected to HPV detection, loss of heterozygosity (LOH) analysis of the chromosome 17p region harbouring p53, genotyping at the p53 codon 72 locus and sequencing of the entire p53 gene to identify somatic mutations. Codon 72 heterozygotes carrying the p53 mutation were further cloned and resequenced to identify the allele harbouring the mutation. Results: HPV positivity in the HNSCC samples was 69%; 21% of the HNSCC were found to harbour p53 mutations in the coding region of the gene. The absence of the p53 mutation in HPV positive tumours was statistically significant compared to the HPV negative tumours (p = 0.01), but the same did not hold true for p53 LOH (p = 1.0). Among the germline p53 codon 72 heterozygotes, the Pro allele was preferentially lost (p = 0.02) while the Arg allele was mutated in the majority of cases. The risk of HPV mediated tumourigenesis increased with the increase in number of Arg alleles at the codon 72 locus. Conclusion: It is proposed that genetic and epigenetic alteration of p53 follow distinct pathways during the development of HNSCC from normal epithelium via dysplasia. The p53 mutation and HPV mediated p53 inactivation possibly constitute two independent pathways of tumourigenesis.